Types and abundance of peripyhton in the glass substrate placed in The Bandar Kayangan Lembah Sari Reservoir, Rumbai Pesisir District, Pekanbaru - Abdi Doly Tarigan; Asmika Harnalin Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractPeriphyton is a sessile microscopic organism that attached on immersed substrates. A research aims to determine the type and abundance of periphyton on glass substrate has been carried out in April-May 2018 in the Bandar Kayangan Lembah Sari Reservoir. There were four sampling stations, namely station 1 (in the inlet, from the Ambang River), station 2 (in the inlet from the Merbau River), station 3 (in the middle of the lake) and station 4 (in the dam). In each station there were two sampling points, 24 glass were immersed (12 pieces in 20 cm depth and 12 pieces in the middle of water column depth). Samplings were conducted 3 times, once/week. Water quality parameters measured were temperature, transparency, pH, dissolved oxygen, free carbon dioxide, nitrate, and phosphate. Results shown that there were 22 types of periphyton present and they were belonged to 4 classes, namely Bacillariophyceae (5 species), Chlorophyceae, (13 species) Cyanophyceae (2 species), and Euglenaphyceae (2 species). The periphyton abundance of Bandar Kayangan Lembah Sari Reservoir was 3,064-15,240 cells/cm2. Based on the abundance of periphyton, trophic state of the Bandar Kayangan Reservoir’s water is eutrophic. The water quality parameters were as follows: temperature: 27.3-29.3°C, transparency: 65.17-74.33 cm, pH: 5, free carbon dioxide: 3.32-4.66 mg/L, dissolved oxygen: 5.87-7.38 mg/L, nitrate: 0.02-0.07 mg/L, and phosphate: 0.03-0.07 mg/L.Keywords: Sessile organism, water quality, glass substrate, man-made lake, Eutrophic